Places of Worship - Villaroman, Noel (Journal of law, religion and state, 2014)
The present paper analyzes the substance of the right to establish and maintain places of worship in order to reveal the elements that make up its conceptual core. First, the process of international standard-setting in human rights is explained, in particular the important contribution of the un Special Rapporteur on Freedom of Religion or Belief to standard-setting. Second, the paper summarizes the outcomes of the standard-setting activities of the un Human Rights Committee and of the Special Rapporteur on Freedom of Religion or Belief with respect to places of worship. The analysis demonstrates the significance of the right to establish and maintain places of worship − a key religious freedom norm which aims to ensure that the structural requirement of religious freedom is adequately met.